Competitive Price Adjustment to Changes in the Money Supply - Eden, Benjamin (Quarterly Journal of Economics, 1982)
In a competitive environment in which (ex ante) identical sellers set prices, the market price cannot always be based on updated information, since otherwise there will be no incentive to gather information about changes in demand. This result is applied to the case in which changes in the money supply are the only source of uncertainty. It is shown that, if the possible changes in the money supply are not large, the economy will exhibit a positive relationship between money and output but no involuntary unemployment. If the possible changes in the money supply are large, the economy will exhibit a positive relationship between money and employment, allowing for involuntary unemployment.